The effect of oral indomethacin on the incidence of cystoid macular edema after cataract surgery with implantation of an intraocular lens. - Suhardjo Suhardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
Cystoid macular edema after cataract extraction with implantation of an intraocular lens is considered to be the most frequent and troublesome complication. The advantage of topical indomethacin had been previously proven, but the influence of oral administration had not been investigated. The purpose of this study is to Investigate the effect of the using of indomethacin on the incidence of cystoid macular edema after cataract surgery with an intraocular lens implantation. Two groups of patients with matured and immatured senile cataract undergone extracapsular cataract extraction with implantation of an intra ocular lens had been reported. Each group consisted of 40 patients. Indomethacin group received 25 mg indomethacin orally 2 hours preoperativelly, as well as at 2, 6, and 10 hours postoperativelly then continued for 5 days postoperativelly. Ocular examinations were performed on postoperative days 1, 3, 7, 14, 28, 60, and 90. No Incidence of cystoid macular edema in group indomethacin was found and in placebo group was 2,5% (x2 = 0,001; p> 0,05). After seven days observation on the effect of indomethacin to the postoperative inflammatory reaction demonstrated that there was insignificantly difference between indomethacin and placebo group (x2 = 2,15; p >0,05). Observation on the therapeutic side effect phenomenon indicated that Indomethacin was relativelly safe even if used in the aged patients.Key Words : oral indomethacin - cystoid macular edema - cataract operation - intra-ocular lens -inflammatory reaction